TANAMAN ROSELA (Hibiscus sabdariffa L) DITINJAU DARI ASPEK PRODUKSI DAN EKOLO0GI - Eladisa Ganjari, Leo (Widya Warta, 2010)
Rosela is a plant already known by society. Generally, some parts of this plant are used as raw materials for food and drink. The parts intended include its flower sheaths (calyx) and the seeds inside fruits. Used as production materials, those parts of Rosela are of great value both economically and medically. In this research Rosela was studied in terms of production and ecology aspects. Production aspect observation was concerned with the determination of weight percentage of flower sheaths, fruits, and seeds, as well as of waning percentage of flower sheaths during dehydration. While, ecology aspect observation dealt with the observation on the change of ecosystem composing components which took place. This study was conducted from August 2008 up to August 2009.The sample of this research was 100 Rosela flower sheaths which were still stuck to the fruits. The result of the research showed that the ratio of average weight percentage of flower sheaths, fruits, seeds, fruits without seeds was 57,39 : 42,61 : 17,62 : 24,98 and dry flower sheaths after the waning process was 90,05. There was a change of ecosystem composing components namely, abiotic components in the form of field function conversion, introductory production components of Hibiscus sabdariffa, human consumer components making use of plants as materials for food, drink, medical product, and introductory consumer of pests namely, Bapak pucung (red bug or Dysdercus cingulatus f), and Aphis gossypii (cotton aphid).